Climate goals and SDGs: Money, that’s what (we) want - Díaz Bonilla, Eugenio (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
Food systems are fundamental in plans and programs aimed at achieving the Sustainable Development Goals (SDGs), as well as the climate mitigation, adaptation, and resilience goals of the Paris Agreement. Therefore, it is important to mobilize sufficient financial resources to cover the costs of such plans and programs. However, current levels of financing, particularly in developing countries, are insufficient to achieve the objectives of the 2030 Agenda for Sustainable Development and the Paris Agreement. Some initiatives are proposed to mobilize additional financing, such as tapping into international development funds (multilateral financial institutions, bilateral aid agencies, and philanthropic groups), national government budgets, banking system operations, and capital market financing. It is highlighted as a limitation of this proposal that most cost estimates and financial proposals are global or for developing countries as a whole.